Financial Disclosure based on Web-ICT Determinants - Hadi, Ahwan; Handajani, Lilik; Putra, I Nyoman Nugraha Ardana (International Research Journal of Management, IT & Social Sciences, 2018)
The purpose of this research is to analyze the influence of local government characteristic and accountability performance on the financial disclosure based on WEB-ICT and how itâs implications for local government financial performance as a response to the public information disclosure requirements. Using 307 regencies and cities local government in Indonesia as samples based on purposive sampling and analyze by SEM-PLS technique. The result shows that local government characteristic and accountability of local government performance has a positive influence on financial disclosure based on web-ICT. It indicates that local governments with better performance accountability levels and have greater or more mature characteristics will disclose wider financial information through the website. These findings are consistent with the signaling theory which states that organizations tend to provide a signal in the form of information disclosure to stakeholders to describe positive conditions. This study also found that financial disclosure based on web-ICT has a negative influence on local government financial performance, public sector characteristics that are nonprofit oriented cause disclosure of financial information does not encourage the financial performance of local government. Unlike the private sector, the disclosure of information encourages better corporate financial performance.